Turkey as BODY POLITIC: A Comparative Perspective on Body-related Metaphors from Turkish, British, and American Political News Discourse - Esranur Efeoğlu; Hale Işık-Güler (Dilbilim Araştırmaları Dergisi)
This study investigates the body politic conceptualization of Turkey in political discourse. A corpus-driven Critical Metaphor Analysis is carried out on the corpus of Political Discourse (POLDIS) which consists of political news articles from Turkish, British and American newspapers. The source domains of "BODY", "LIFE", and "HEALTH" are mapped into the target domain: "TURKEY". The manifested general metaphor "A COUNTRY IS AN ANIMATE BEING" and its sub-metaphors are described for both languages. The comparative results show that the conceptual metaphors used for Turkey are in line between both languages, yet the frequency and the resonance of the source domains differ. Adding on to the existing literature, language specific source concepts, such as "FATE" in Turkish and "HANDICAP" in English are identified. The study is preliminary in the sense that it describes how Turkey as a sociopolitical entity is conceptualized in Turkish and English political discourse.